2022
DOI: 10.36660/abc.20210670
|View full text |Cite
|
Sign up to set email alerts
|

O Valor Preditivo do Escore CHA2DS2-VASc no Escore Syntax Residual em Pacientes com Infarto do Miocárdio com Supradesnivelamento do Segmento ST

Abstract: Fundamento: O escore CHA2DS2-VASc está associado a desfechos clínicos adversos em pacientes com doença cardiovascular. O escore Syntax residual (residual Syntax score -rSS) é uma ferramenta de pontuação que tem valor prognóstico em pacientes com infarto agudo do miocárdio com supradesnivelamento do segmento ST (IAMCSST). Objetivos: Este estudo objetivou investigar o valor preditivo do escore CHA2DS2-VASc para o rSS em pacientes com IAMCSST. Métodos: Foram avaliados 688 pacientes consecutivos com IAMCSST submet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 15 publications
0
5
0
1
Order By: Relevance
“…One theoretical benefit of coronary artery bypass graft over PCI relies on the idea that the graft bypasses long segments of proximal coronary plaques, and the patient would be protected from MI if any of those ruptures, whereas the stents protect only the stented segment. 14 In conclusion, Kalkan et al 8 demonstrated that patients with higher CHA 2 DS 2 VASc score have higher rSS, which means higher CAD severity. Based on recent evidence, those patients might consequently be at higher risk of plaque rupture and cardiovascular events, such as MI or death, and therefore would benefit from more aggressive plaque stabilizing therapies.…”
mentioning
confidence: 85%
See 2 more Smart Citations
“…One theoretical benefit of coronary artery bypass graft over PCI relies on the idea that the graft bypasses long segments of proximal coronary plaques, and the patient would be protected from MI if any of those ruptures, whereas the stents protect only the stented segment. 14 In conclusion, Kalkan et al 8 demonstrated that patients with higher CHA 2 DS 2 VASc score have higher rSS, which means higher CAD severity. Based on recent evidence, those patients might consequently be at higher risk of plaque rupture and cardiovascular events, such as MI or death, and therefore would benefit from more aggressive plaque stabilizing therapies.…”
mentioning
confidence: 85%
“…A high rSS was associated with a poor 30-day and 1-year prognosis. 7 In this issue of Arquivos Brasileiros de Cardiologia, Kalkan et al 8 demonstrated for the first time the association between CHA 2 DS 2 VASc score and rSS in 688 patients who underwent primary PCI after STEMI. 8 Although it seems obvious to find a relationship between a score that includes some of the main risk factors for atherosclerosis (CHA 2 DS 2 VASc) and the atherosclerotic burden itself (rSS), it brings our attention to the relevant and contemporary discussion about the importance of the severity of atherosclerosis.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…O trabalho realizado por Kalkan et al, 1 teve por objetivo avaliar o valor preditivo do escore CHA2DS2-VASc para o escore syntax residual (rSS) em pacientes com infarto agudo do miocárdio com supradesnivelamento do segmento ST (IAMCSST). 688 pacientes foram incluídos no estudo, os quais foram divididos em dois grupos a considerar o escore rSS: pontuação até 8: grupo de rSS baixo (grupo 1); pontuação acima de 8: grupo de rSS elevado (grupo 2).…”
unclassified
“…Kalkan et al 1 assessed the predictive value of the congestive heart failure, hypertension, age, diabetes mellitus, prior stroke, vascular disease, age, sex category (CHA 2 DS 2 -VASc) score for residual SYNTAX score (rSS) among patients with ST-segment elevation acute myocardial infarction (STEMI). The study included 688 patients divided into a low rSS group (group 1; scores up to 8) and a high rSS group (group 2; scores above 8).…”
mentioning
confidence: 99%